Geomorphosite assessment - Bojan Erhartič (Acta Geographica Slovenica, 2010)
Geomorphosites comprise natural features and processes, which can carry a certain value, whether that be scientific, aesthetic, historical, cultural, social, economic or other. With the intention of reducing the subjective impacts and enabling a mutual comparison, several assessment methods burst onto the scene. The article mentions four procedures of geomorphosite assessment on the basis of Slovene methodology. Which assessment method seems most adequate, depends on the research aims. For the needs of nature protection, greater emphasis should be put on scientific and management aspects, with additional emphasis on the social component or the cultural value to guarantee a more comprehensive study.